The Effect of Iron and Vanadium in VOy/Ce1‐xFexO2‐δ Catalysts in Low‐Temperature Selective Catalytic Reduction of NOx by Ammonia. Issue 9 (27th February 2020) - Keller, Sonja; Agostini, Giovanni; Antoni, Hendrik; Kreyenschulte, Carsten R.; Atia, Hanan; Rabeah, Jabor; Bentrup, Ursula; Brückner, Angelika
Abstract: Supported VOy /Ce1‐x Fex O2‐δ catalysts (x=0, 0.5, 0.1, 0.2) and bare supports were prepared and tested in selective catalytic reduction (SCR) of NOx by NH3 between 150 and 300 °C with a GHSV of 70 000 h −1 . Iron was found to be beneficial for the activity of the pristine supports, reaching 80 % conversion at 275 °C. When vanadium was additionally introduced into the system, iron was found to be detrimental for NOx ‐conversion. To derive structure‐reactivity relationships, V‐free supports and VOy /Ce1‐x Fex O2‐δ catalysts were characterized by XRD, XPS, Raman spectroscopy and TEM. In situ XANES, as well as operando DRIFTS and EPR measurements were performed to study the behavior of the catalysts under reaction conditions. Up to an iron content of x=0.1, a solid Ce1‐x Fex O2‐δ solution was formed. Higher iron contents led to formation of iron oxide agglomerates. These agglomerates, as well as an increased amount of surface oxygen species were found to be responsible for increased NOx ‐conversion over of pure supports. For V‐containing catalysts, an interaction of Fe and V centers could be found. Under reaction conditions, Fe 3+ was preferentially reduced instead of V 5+, decreasing the catalytic activity of VOy /Ce1‐x Fex O2‐δ . Abstract : The cover picture shows that NOx removal from exhaust gases is very fast with catalysts containing vanadia supported on ceria while iron in the ceria support "throughs a wrench in the works". In their Full Paper on p. XX ff., Angelika Brückner et al. show that iron boosts activity of bare Ce1‐x Fex O2‐δ solid solutions while, unexpectedly, it is detrimental when vanadia is supported on their surface. In situ XANES, operando DRIFTS and EPR studies showed that Fe 3+ is partly reduced to inactive Fe 2+, favours clustering of VOy sites and damages active V‐O‐Ce junctions.